Economie agricole vs paysage. Experience du MONTADO portugais - PInto-Correia, Teresa (2013)
This lecture adressses the multifunctionaloty of the MOntdao, an agro-silvo pastoral systems chracteristic of Southern Portugal, similar to the DEhesa and Spain. It considers the multiple management possibilities emerging from the multifunctionality of the system and the need to suport land owners for achievinga truly multifunctional management